Study of caloric value in Cyclobanopsis glauce population - NI Sui; CHEN Qi-chang (浙江大学学报. 农业与生命科学版)
Caloric values of leaf, branch and stem are different with various diameter-classes of Cyclobanopsis glauca population. To the same trophic organ in the same diameter-class, the seedling's caloric value is greater than that of coppice, and the difference between them decreases with the increase of diameter-classes. Caloric values of various layers of Cyclobanopsis glauca population trophic organs shows: leaf>branch>stem.